The Chaitenia accretionary orogen of northwest Patagonia: new U-Pb SHRIMP ages of the Foreland Domain - Rapela, Carlos Washington (2022)
The Andean basement of NW Patagonia between 39º and 43º S contains remnants of Devonian plutonic, volcanic and metamorphic rocks. While some of them were clearly emplaced in continental crust at the easternmost edge of North Patagonian Massif, in the west of the North Patagonian Cordillera and the coastal region, the igneous rocks were developed in an oceanic environment. Thus, a Foreland Devonian Domain (FDD) and a Pacifi c Devonian Domain (PDD) are distinguished on either side of the modern Andean Cordillera (Fig. 1). While the Devonian granites of the Foreland Domain can be unambiguously ascribed to subduction in a continental margin (see references in Rapela et al. 2021), the more scattered outcrops of pillow lavas, alkaline trachyte-rhyolite and primitive granites of the PDD required more detailed studies to determine their petrogenesis and tectonic signifi cance. Initial studies suggested that they represented the mixed products of an oceanic island arc that later became accreted to the continent as an allochthonous terrane (the Chaitenia terrane of Hervé et al. 2016). However, whole-rock geochemistry shows that the pillow lavas are dominated by back-arc basalts and that metasandstones interbedded with the pillow lavas contain detrital zircons with U-Pb ages, Hf and O isotope compositions comparable to those of the Foreland Domain granites, i.e., they are of contemporary continental provenance. Thus, they are more likely to represent a Devonian parautochthonous terrane, formed after continental rifting and was laterally accreted during closure of a back-arc basin in an orogen that also encompasses the fore-arc (Rapela et al. 2021), and which we now refer to as the Chaitenia Accretionary Orogen (CAO). Five stages have been recognized in its evolution: (i) a continental arc stage that involved the San Martín arc (c. 405-395 Ma, Emsian); (ii) a forearc rift-ridge transition stage (c. 395-390 Ma, Emsian-Eifelian); (iii) a marginal basin stage that involves the starting of an oceanic arc, the Chaitenia arc (c. 380-390 Ma, Eifelian-Givetian); (iv) a double arc stage (365-380 Ma, Giovetian-Frasnian) and (v) closing of the Chaitenia marginal basin (c. 360-340 Ma, Fammenian-Visean).